DETERMINANTS OF LEARNING ORIENTATION AND MOTIVATION ON EMPLOYEES PERFORMANCE - Sri Ismulyaty; Etty Puji Lestari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Sri Ismulyaty dan Etty Puji Lestari; The company's goal is to develop a variety of marketing strategies to improve the profitability of the company, so the company's management to focus on efforts to identify the customer, because the philosophy of marketing shows that the profit can be created through the satisfaction perceived by customers. Work motivation is believed to be influential in arousing, directing, and maintaining behavior in the work environment to develop achievement. Several studies have suggested a link between work motivation with employee performance. The purpose of this study was to analyze the influence of learning orientationof 46 employee performance at the Open University. We used stratified random sampling method. Data used in this study were primary data from the respondents and secondary data. The results showed that there is a positive relationship between learning orientation with employee performance shown by the value of the original sample estimate of 0.854 and a t-statistic of 4,228 is greater than the t-test is 1.96. While the relationship work motivation and performance have negative impact.Keywords : learning orientation, motivation, performance